Ceramide Is Responsible for the Failure of Compensatory Nerve Sprouting in Apolipoprotein E Knock-Out Mice - Maysinger, Dusica (J Neurosci, 2008)
Apolipoprotein E (apoE) is a key transporter of the cholesterol and phospholipids required for membrane synthesis and nerve growth. We now report a virtual absence in apoE knock-out (KO) mice of normal nerve growth factor (NGF)-driven compensatory sprouting of undamaged cutaneous nociceptive nerves. In contrast, NGF-independent regeneration of crushed axons was unaffected. Essentially similar results came from aged wild-type mice. In apoE KO mice, the endogenous sprouting stimulus was suspect, because NGF administration induced normal sprouting; nevertheless, NGF increased normally in denervated skin, transported normally in the axons, and led to phosphorylation of trkA, erk1, and erk2. However, sprouting was restored in apoE KO mice (although not in aged mice) by fumonisin B1, an inhibitor of ceramide synthesis. A shotgun analysis revealed a wide array of changes in individual ceramide species in DRG neurons of apoE KO mice, and the changes for ceramide species OH_N15:0 made it a candidate inhibitor of sprouting (increased in apoE KO mice and normalized by fumonisin B1). Nevertheless, the unknown effects of individual ceramide species on sprouting, as well as the variability of their changed levels in apoE KO mice and how these were affected by fumonisin B1, support a different conclusion. We suggest that absence of apoE expression alters the balance among ceramide species to one that collectively inhibits compensatory sprouting, whereas fumonisin B1 establishes a new balance that allows sprouting. Nontoxic ceramide modulators might usefully promote sprouting and circuitry repair in neurodegenerative disorders in which ceramide species are perturbed, adding to the benefits of reducing ceramide-induced neuronal apoptosis.